Non-Parametric Analysis of Factors Influencing Maximum Heart Rate in the Healthcare Sector - Tanubrata, Nicholas Andrew; Sambow, William Samuel; Christian, Jonathan; Ferdinand, Ferry Vincenttius (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2024)
This study aims to analyze factors that influence maximum heart rate using a non-parametric statistical analysis approach, which is flexible in analyzing data with unknown or non-normal distributions. Factors analyzed include resting electrocardiogram (ECG) examination results, type of chest pain, and blood pressure. Respondents were classified based on these factors to facilitate analysis. Methods used in this study included the Expanded Median Test (K-Sample), Pearson Correlation Test, and Kruskal-Wallis Test, which were chosen because they were appropriate for the type of data and the objectives of the study that involved testing the median between multiple groups. Results showed that ECG and chest pain type significantly influenced maximum heart rate, while blood pressure did not show a significant effect. The main contribution of this study is that it provides an empirical basis for detecting modifiable cardiovascular risk factors, supporting heart attack prevention efforts through early detection, and directing further research for a more comprehensive analysis.Bahasa Indonesia Abstract:Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi detak jantung maksimum menggunakan pendekatan analisis statistik non-parametrik, yang fleksibel dalam menganalisis data dengan distribusi yang tidak diketahui atau tidak normal. Faktor yang dianalisis meliputi hasil pemeriksaan elektrokardiogram (EKG) istirahat, tipe nyeri dada, dan tekanan darah. Responden diklasifikasikan ke dalam kelompok risiko berdasarkan faktor-faktor ini untuk memudahkan analisis. Metode yang digunakan dalam penelitian ini mencakup Perluasan Uji Median (K-Sampel), Uji Korelasi Pearson, dan Uji Kruskal-Wallis, yang dipilih karena sesuai dengan jenis data dan tujuan penelitian yang melibatkan pengujian median antara beberapa kelompok. Hasil menunjukkan bahwa EKG dan tipe nyeri dada secara signifikan memengaruhi detak jantung maksimum, sedangkan tekanan darah tidak menunjukkan pengaruh signifikan. Kontribusi utama penelitian ini adalah memberikan dasar empiris untuk mendeteksi faktor risiko kardiovaskular yang dapat dimodifikasi, mendukung upaya pencegahan serangan jantung melalui deteksi dini, dan mengarahkan penelitian lanjutan untuk analisis yang lebih komprehensif.